Good University Governance Oriented of Change Management, Management, Budgeting System, and Behavioral Aspect - G. S. Budiwitjaksono; E. Andhaniwati; L. Romaisyah (Future Science)
This study aims to identify several indicators as a consequence of organizational change into a New State University, both in term of the financial management system, change management and member behavior to realize Good University Governance. This study used a qualitative approach with the leaders in the UPN Veteran East Java environment as the research object which determined based on their involvement in financial management and budgeting processes. The results of the study explain that to realize Good University Governance that takes into accountability, transparency, responsibility, and fairness aspects, it is necessary to strengthen the implementation of financial management systems, adequate change management, and strong commitment from the leaders in controlling the behavior of the organization member.